Corrosion of Aluminium Metal in Food Environments and its Associated Health Risk Issues: A Review - Guma, T. N.; Maikudi, M. M. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2023)
A material for use in contact with food must have adequate strength and integrity to avoid its accidental fracture and leaching of pernicious substances into the food due to corrosion or abrasion of the material. This review covers the basics of aluminium metal and its corrosion in food-handling usage and the associated health-risk issues of its particle intake by human food consumers, as well as current research on the topic. The review findings show that aluminium metal has outstanding advantages in food handling in terms of low cost, wide availability, light weight, ability to heat and cool fast, high temperature tolerance, good corrosion resistance, and perennial shiny appearance in unpolluted natural environments. Its other advantage is excellent formability into designed kitchenware shapes. On the other hand, the findings show that aluminium metal has lower strength and hardness integrity. It is also leachable with lower health-safety level for food-handling usage compared to many other food-grade metals such as stainless steel. Furthermore, daily intake of aluminium substances above 10 mg per kilogram by an individual is risky to their health. The other findings are that food environments with high chloride, acidity, and alkalinity contents can cause greater corrosion of aluminium metal to leach its particles into food, with a higher chance of intaking the particles into the human body system than other food environments. Finally, the findings show that only appropriately alloyed and adequately coated aluminium of sufficient strength should be used in contact with food. The information from the review is meant to serve as a consolidated current literature position on corrosion in the use of aluminium metal for food handling and associated health-risk issues for safe-guarding or a way forward by researchers and stakeholders that need background information for making the metal safer for food handling.